Phlebotomus argentipes : possible vector of leishmaniasis in Sri Lanka - Senanayake, S.A.S.C.; Abeyewickreme, W.; Abeysinghe, R.R.; Dotson, E.M.; Karunaweera, N.D. (University of Colombo, 2011)
Leishmaniasis is caused by a protozoan parasite belonging to the genus Leishmania. The disease is transmitted via infective the bite of female phlebotomine sandflies. The disease has three clinical presentations depending on the different tissues involved (skin ± cutaneous leishmaniasis (CL), mucous membranes ± mucocutaneous leishmaniasis (MCL) and internal organs ± visceral leishmaniasis (VL). Leishmaniasis is endemic in more than 90 countries including neighboring countries like India, Bangladesh, Nepal and Pakistan. CL is prevalent in many parts of Sri Lanka and has become an established disease in the country. A few cases of visceral leishmaniasis are also reported and many more cases may be awaiting diagnosis. The causative organism of Sri Lankan CL was confirmed as Leishmania donovani MON 37. The true vectors of leishmaniasis in Sri Lanka are still under investigation and no concrete evidence has surfaced even though the potential vector Phlebotomus argentipes was reported in 1910. The researchers carried out a field study on vector aspects of leishmaniasis in a selected pocket where there were many reported cases of CL. The objectives were to describe the distribution of various species of sandflies in the area and to identify the true vectors of leishmaniasis in Sri Lanka